Konsep Paradoks Kepemimpinan pada Lembaga Pendidikan dalam Pengambilan Keputusan - Sukmawati, Sukmawati; Hamdi, Miftahul; Yakin, Nurul (ARZUSIN, 2022)
Leadership can be interpreted as a process of fostering a reciprocal relationship between leaders and those who are led by relying on interpersonal communication skills so that mutual understanding and cooperation between personnel are established according to the responsibilities and tasks that have been set. The leadership that each leader has will have a major influence on the achievement of educational goals. Leadership in education has a very important role, considering the function of the leader is to determine the achievement of educational goals. Basically every institution or educational institution requires a figure (leader) who will guide and direct the implementation of education at the institution. This type of leadership is also influenced by the style applied by someone who leads. An organization will succeed or fail largely determined by the leadership of the institution itself, including in educational institutions.